Stockholding: From participation to location and to participation spillovers - Dimitris Christelis; Dimitris Georgarakos; Michael Haliassos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
This paper provides a joint analysis of household stockholding participation, stock location among stockholding modes, and participation spillovers, using data from the US Survey of Consumer Finances. Our multivariate choice model matches observed participation rates, conditional and unconditional, and asset location patterns. Financial education and sophistication strongly affect direct stockholding and mutual fund participation, while social interactions affect stockholding through retirement accounts only. Household characteristics influence stockholding through retirement accounts conditional on owning retirement accounts, unlike what happens with stockholding through mutual funds. Although stockholding is more common among retirement account owners, this fact is mainly due to their characteristics that led them to buy retirement accounts in the first place rather than to any informational advantages gained through retirement account ownership itself. Finally, our results suggest that, taking stockholding as given, stock location is not arbitrary but crucially depends on investor characteristics.
urn:nbn:de:hebis:30-63730
Keywords: G11; E21; D14; C35; 330; Stockholding; Asset Location; Retirement Accounts; Household Finance; Multivariate Probit; Simulated Maximum Likelihood; Privater Haushalt; Anlageverhalten; Aktionäre; Private Rentenversicherung; USA